The Epigenetic Mechanisms of Amphetamine - McCowan, Talus J. (J Addict Prev, 2015)
Amphetamine (AMPH) is a psychostimulant and the most prescribed drug to treat attention deficit hyperactive disorder (ADHD). Although therapeutically used doses are generally well tolerated, numerous side effects are still known to occur, such as jitteriness, loss of appetite and psychosis. Moreover, AMPH is liable to be abused by users looking for increased alertness, weight loss or athletic performance. A growing body of evidence indicates that drugs of abuse, including AMPH, control gene expression through chromatin modifications. However, while numerous studies have investigated the molecular mechanisms of AMPH action, only a small number of studies have explored changes in gene expression caused by AMPH. This review examines the epigenetic changes induced by chronic and acute treatments with AMPH and includes, where relevant, data obtained with other psychostimulants such as methamphetamine and cocaine.